Health-related quality of life in ADHD: a pooled analysis of gender differences in five atomoxetine trials - Wehmeier, Peter M.; Schacht, Alexander; Escobar, Rodrigo (ADHD Attention Deficit and Hyperactivity Disorders, 2012)
Attention-deficit/hyperactivity disorder (ADHD) is associated with considerable impairment in health-related quality of life (HR-QoL). Atomoxetine has been found to improve HR-QoL in both children and adolescents. However, there is scarcity of data on gender differences in treatment responses to ADHD medications. This pooled analysis of five atomoxetine trials aimed to evaluate treatment differences with respect to HR-QoL and ADHD symptoms across genders. Data from 5 clinical atomoxetine trials (4 from Europe and 1 from Canada) with similar inclusion and exclusion criteria and similar durations (8- to 12-week follow-up) were included in the pooled analysis. All studies included the Child Health and Illness Profile—Child Edition (CHIP-CE) Parent Report Form. In addition, correlations between HR-QoL and ADHD core symptoms were compared between girls and boys. Data from 136 girls and 658 boys (mean age: 9.6 and 9.7 years, respectively) were pooled. Boys and girls were similarly impaired at baseline with minor differences in some of the subdomains. Treatment effect of atomoxetine was significant in both groups for the Risk Avoidance domain and its subdomains. No gender effect with both clinical and statistical significance was found for treatment outcome. Correlations between ADHD Rating Scale and CHIP-CE scores were similar in both genders and were generally low at baseline and moderate at endpoint and for the change from baseline to endpoint. Atomoxetine was effective in improving some aspects of HR-QoL in both genders without any significant differences across genders. Correlations between core symptoms of ADHD and HR-QoL were low to moderate in both boys and girls.
Gesehen am 29.04.2019